ANALISIS PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DALAM MENYEDIAKAN RUMAH LAYAK HUNI DI KELURAHAN BEROHOL KECAMATAN BAJENIS KOTA TEBING TINGGI - Dewi Herlina; Zuhrinal M. Nawawi; Tuti Anggraini (Studia Economica : Jurnal Ekonomi Islam, 2021)
This study aims to determine the implementation of Self-Help Housing Stimulant Assistance (BSPS) in providing livable houses in Berohol Village, Bajenis District, Tebing Tinggi City. Self-Help Housing Stimulant Assistance (BSPS) is a government facility in the form of stimulant assistance for the construction / improvement of housing quality provided to low-income people. Low-Income Communities (MBR) are people who have limited purchasing power so they need government support to get a decent house to live in. Self-Help Housing are houses built on the initiative and efforts of the community, either individually or in groups. This type of research is a descriptive qualitative research. In collecting research data using interview techniques, observation, and documentation using informants as a source of information. The results of this study indicate that the implementation of the Self-Help Housing Stimulant Assistance Program in providing Liveable Homes in Berohol Village, Bajenis District, Tebing Tinggi City has not been optimal. Including the distribution of BSPS that has not been on target, lack of participation and public awareness and lack of knowledge about the BSPS program. In addition, in the development stage, it should be carried out cooperatively with fellow groups that have been determined but in reality it is still done individually. Researchers also see that the implementors in the implementation of the BSPS Program in Kelurahan Berohol still do not have firmness because they still allow the community to work individually. Even though they understand what the concept and purpose of the BSPS program actually is.